Single-Sided Microwave Near-Field Scanning of Pine Wood Lumber for Defect Detection - Mohamed Radwan (MDPI AG, 2021)
Defects and cracks in dried natural timber (relative permittivity 2–5) may cause structural weakness and enhanced warping in structural beams. For a pine wood beam (1200 mm × 70 mm × 70 mm), microwave reflection (S11) and transmission (S21) measurements using a cavity-backed slot antenna on the wood surface showed the variations caused by imperfections and defects in the wood. Reflection measurements at 4.4 GHz increased (>5 dB) above a major knot evident on the wood surface when the E-field was parallel to the wood grain. Similar results were observed for air cavities, independent of depth from the wood surface. The presence of a metal bolt in an air hole increased S11 by 2 dB. In comparison, transmission measurements (S21) were increased by 6 dB for a metal screw centered in the cavity. A kiln-dried pine wood sample was saturated with water to increase its moisture content from 17% to 138%. Both parallel and perpendicular E-field measurements showed a difference of more than 15 dB above an open saw-cut slot in the water-saturated beam. The insertion of a brass plate in the open slot created a 7 dB rise in the S11 measurement (p < 0.0003), while there was no significant variation for perpendicular orientation. By measuring the reflection coefficient, it was possible to detect the location of a crack through a change in its magnitude without a noticeable change (<0.01 GHz) in resonant frequency. These microwave measurements offer a simple, single-frequency non-destructive testing method of structural timber in situ, when one or more plane faces are accessible for direct antenna contact.